Comparative evaluation of genotoxicity in tobacco users versus nontobacco users - Arun Jacob Thomas; Bindu J Nair; Sajna Oommen; V Syamkumar; Resmi K Raman (Wolters Kluwer Medknow Publications, 2021)
Background: Many of the contents of cigarette smoke are genotoxic in nature, and consequently, cytogenetic injury seems to be a trustworthy biomarker for deciding the influence of exposure to chromosome damaging agents in smoke. The cytokinesis-block micronucleus assay (CBMN assay) has been proven to be an effectual tool for the study of micronuclei (MN) that will help in estimating the genotoxicity in tobacco users alone which will further help in early cancer detection. Objective: The objective is to find out whether there is pronounced contrast in genotoxicity between tobacco users and nonusers by determining MN number in peripheral blood lymphocytes using CBMN assay. Methodology: MN frequency in peripheral blood lymphocytes was estimated in 5 ml of fresh blood obtained from sixty individuals using tobacco either smoking, chewing, or combination of both and also from thirty individuals with no habit of tobacco use. All were in the age group of 20-40 years. Results: There was a significant increase in genotoxicity in tobacco users when compared to that of nontobacco users. A positive correlation was also obtained between smoking index and MN frequency in the study. Conclusion: Approximation of frequency of MN by CBMN assay can be used to evaluate the genotoxicity present in blood and helps in identifying tobacco users who are at a high risk for the presence of cancer even before the appearance of clinical changes.